Linear convergence of gradient projection algorithm for split equality problems. (2nd December 2018) - Shi, Luo-Yi; Ansari, Qamrul Hasan; Yao, Jen-Chih; Wen, Ching-Feng
ABSTRACT: In this paper, we consider the varying stepsize gradient projection algorithm (GPA) for solving the split equality problem (SEP) in Hilbert spaces, and study its linear convergence. In particular, we introduce a notion of bounded linear regularity property for the SEP, and use it to establish the linear convergence property for the varying stepsize GPA. We provide some mild sufficient conditions to ensure the bounded linear regularity property, and then conclude the linear convergence rate of the varying stepsize GPA. To the best of our knowledge, this is the first work to study the linear convergence for the SEP.